1998
DOI: 10.1093/brain/121.12.2341
|View full text |Cite
|
Sign up to set email alerts
|

A clinicogenetic analysis of six Indian spinocerebellar ataxia (SCA2) pedigrees. The significance of slow saccades in diagnosis

Abstract: Clinical revaluation and genetic analysis of six Indian pedigrees, segregating autosomal dominant cerebellar ataxia, slow saccades and peripheral neuropathy, has been undertaken, and expansion at the spinocerebellar ataxia 2 (SCA2) locus was confirmed in 14 affected family members. These families became available from 31 phenotypically similar families seen over the years. In common with other neurodegenerative disorders resulting from expansion of a CAG trinucleotide repeat motif, an inverse correlation betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 38 publications
3
53
0
Order By: Relevance
“…This work was carried out at a time when not only had the advanced genetics techniques available to us today not been developed, but also there was not even an adequate system for classifying the various entities that were being discovered. The most important contribution by Prof. Wadia was the identification, for the first time, of spinocerebellar ataxia with slow eye movements, nowadays defined as SCA 2 [4][5][6][7] .…”
Section: Wadia's Contributions To Neurologymentioning
confidence: 99%
See 2 more Smart Citations
“…This work was carried out at a time when not only had the advanced genetics techniques available to us today not been developed, but also there was not even an adequate system for classifying the various entities that were being discovered. The most important contribution by Prof. Wadia was the identification, for the first time, of spinocerebellar ataxia with slow eye movements, nowadays defined as SCA 2 [4][5][6][7] .…”
Section: Wadia's Contributions To Neurologymentioning
confidence: 99%
“…The presence of cerebellar atrophy was suggested but not confirmed because a pathological study was not carried out and the only imaging examination available at the time was pneumoencephalography 4 . His interest in the disease, which was later called SCA 2, led to the publication, in 1975, of a model of an ocular subsystem based on his findings in these same patients 6,7 . In the following years he was able to establish a correlation between clinical findings up to that time and olivopontocerebellar atrophy 7 .…”
Section: Spinocerebellar Ataxia Type 2 -Wadia's Seminal Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This feature called attention to Wadia and Swami when made the first report of SCA2 in 1971, so that they described the disease as "a new form of heredofamilial spinocerebellar degeneration with slow eye movements" (Wadia & Swami, 1971). Several clinical and epidemiological studies have confirmed the high frequency of this saccadic alteration in more than 80% of cases (Velazquez-PĂ©rez et al, 2009a;Orozco et al, 1989;Cancel et al, 1997, Wadia et al, 1998Schmitz-HĂŒbsch, et al, 2008).…”
Section: Spinocerebellar Ataxia Type 2 (Sca2)mentioning
confidence: 99%
“…Recently Takano et al 12 have reported that the general prevalence of SCA1 and SCA2 is significantly higher among white SCA pedigrees (15% and 14%, respectively) than in the Japanese (3% and 5% respectively), whereas relative prevalence of SCA3 is higher in the Japanese pedigrees (43%) than in whites (30%). Also, SCA6 appear to be less frequent in white populations (5%) than in Japanese populations (11%) respectively 12 It has been reported that SCA2 is exclusively responsible for all ataxia cases in the Indian population 13 . In a study of six Indian SCA2 pedigrees, Wadia et al 13 observed CAG repeat expansion in 14 affected family members at the SCA2 locus.…”
mentioning
confidence: 99%